Research Advances in Electrochemical Synthesis of Spirocyclic Skeleton Compounds - Wang, Qian; Liu, Han-Fu; Ren, Sai-Yan; He, Mu-Xue; Pan, Ying-Ming (Synthesis, 2023)
Spirocyclic compounds have attracted the interest of synthetic chemists because of their unique ring systems and utility in drug discovery. Many natural compounds containing spirocyclic moieties in their skeleton are effective pharmaceuticals. For many redox processes, electroorganic synthesis is considered an environmentally friendly method, since the use of reagents with significant toxicity is replaced by electric current, so the amount of waste is often greatly reduced. Therefore, this review summarizes the construction of compounds with a spirocyclic skeleton via electrochemical synthesis strategies since 2000.1 Introduction2 Electrochemically Mediated Synthesis of Spirocyclopropanes3 Electrochemically Mediated Synthesis of Spirooxindoles4 Electrochemically Mediated Synthesis of Spirodienones5 Electrochemically Mediated Synthesis of Other Heterospirocycles6 Conclusion
Keywords: electrochemical synthesis; spirocyclic skeleton; spirocyclopropane; spirooxindole; spirodienone